A convenient and quantitative route to Sn(iv)–M [M = Ti(iv), Nb(v), Ta(v)] heterobimetallic precursors for dense mixed-metal oxide ceramics. Issue 15 (13th March 2015) - Mishra, Shashank; Jeanneau, Erwann; Mangematin, Stéphane; Chermette, Henry; Poor Kalhor, Mahboubeh; Bonnefont, Guillaume; Fantozzi, Gilbert; Le Floch, Sylvie; Pailhes, Stéphane; Daniele, Stéphane
Abstract : Simplicity is beauty. Reactions of SnCl4 with M(OR) x yield novel heterobimetallics with simple addition formula. Abstract : The strategy of reacting SnCl4 with M(OR) x provided a convenient and quantitative approach to new heterobimetallics with a simple addition formula, [SnCl4 M(OR) x (HOR) y ] (M = Ti, Nb, Ta; R = Et, Pr i, x = 4, 5; y = 0–2) or sometimes an oxo complex [SnCl3 (O)Ti2 (OPr i )7 (HOPr i )2 ]. The alcoholysis reactions of these heterometallics afforded mixed alkoxo complexes [SnCl4 (μ-OEt)2 M(Pr i O) x (Pr i OH) y ] [M = Ti ( x = y = 2), Nb, Ta ( x = 3, y = 1)] under mild conditions, or a planar rectangular oxo product [SnCl3 (μ-OEt)2 Nb(OEt)2 (EtOH)(μ-O)]2 at refluxing/extended stirring time. DFT calculations shed light on the stability and reactivity of these complexes. The use of these thoroughly characterized heterometallics as sol–gel precursors suppresses the formation of the undesired SnO2 grains, which are difficult to be sintered to a high density. The combined approach of using bottom-up synthesis of mixed Ti0.5 Sn0.5 O2 nanoparticles and Spark Plasma Sintering allowed the successful densification of chloride-free mixed-metal oxide ceramics. The influence of thermal treatment before sintering on the density and spinodal decomposition of the TiO2 –SnO2 pellets is reported.